Dietary mannitol increased the absorption of calcium and magnesium in rats. Issue 4 (5th February 2016) - Xiao, J.; Sakaguchi, E.; Min, X.; Kawasaki, K.
Summary: The effect of mannitol on bone‐related mineral absorption and retention and the mechanism was investigated in this study. Fourteen 8‐week‐old male Wistar rats in experiment 1 and same number and age cecectomized Wistar male rats in experiment 2 were divided into two subgroups of seven animals, respectively, fed diets containing 0 or 4% mannitol for 28 days. Mineral balance tests were determined twice during days 8–12 and days 22–26, and the rats were slaughtered on day 28 both in experiment 1 and experiment 2. The whole caecum and colon were collected with the content to analyse tissue weight, content weight, content's pH and moisture, organic acids' concentration and mineral levels. In experiment 1, Ca absorption and retention and Mg absorption were significantly increased by mannitol feeding during days 8–12. Caecal total weight, tissue weight and content weight were increased, the pH of caecum and colon was reduced, and the concentrations of caecal short‐chain fatty acids (SCFAs) were modified by mannitol feeding. In experiment 2, during days 8–12 and days 22–26, Ca absorption and retention were significantly lowered by mannitol feeding in cecectomized rats; however, mannitol feeding decreased Mg absorption during days 8–12, but did not impact Mg retention. Colonic total weight, tissue weight and content weight were significantly increased, and colonic pH was reduced by mannitol feeding. In conclusion, dietary mannitol increased the absorption of Ca and Mg and the caecum markedly contributed to this promoting effect of mannitol.